Cumulative IVF outcomes after retrieval of testicular spermatozoa: should we use immotile spermatozoa for ICSI?. Issue 2 (August 2021) - Aizer, Adva; Lazarovich, Alon; Dratviman-Storobinsky, Olga; Noach-Hirsh, Meirav; Haas, Jigal; Jacob, Avi; Raviv, Gil; Orvieto, Raoul
Abstract: Research question: What are the cumulative clinical pregnancy rates (CPR) and live births rates (LBR) in intracytoplasmic sperm injection (ICSI) cycles using testicular motile compared with immotile spermatozoa, obtained from testicular sperm aspiration (TESA) or extraction (TESE)? Design: A retrospective analysis of ICSI cycles using TESA or TESE over a period of 7 years. Cycles were divided into two groups according to the motility of the retrieved spermatozoa: Group A consisted of couples with motile spermatozoa; Group B of couples with immotile spermatozoa. Group B was subdivided into two groups: B1 consisted of couples with motile spermatozoa and B2 with immotile spermatozoa after the addition of pentoxifylline. Results: No differences in CPR and LBR per transfer was found between the study groups after fresh embryo transfer. No pregnancies were achieved by vitrified–warmed embryo transfer in group B2. Fertilization rates decreased when using immotile spermatozoa (64.4%, 56%, 37.9%, for groups A, B1 and B2, respectively, P < 0.001). Top-quality embryo rates were higher in groups A and B1 compared with B2 (40.7% and 40.1% versus 19.1%, respectively, P = 0.015). Cumulative CPR (53%, 41.7%, 13.6% for groups A, B1 and B2, respectively, P = 0.005) and LBR (42.4%, 30%, 13.6% for groups A, B1 and B2, respectively P = 0.03) per oocyte retrieval was significantly higher when using motile spermatozoa compared with motile or immotile spermatozoa after adding pentoxifylline. Conclusions: Although fertilization, top-quality embryo rates, cumulative CPR and LBR decreased when using immotile spermatozoa, ICSI is still valid; therefore, it should be considered and offered to couples before embarking on a donor sperm insemination cycle, or cryopreserving oocytes for future additional testicular sperm retrieval.